The Effect of PbSe Addition on the Mechanical Properties of Bi-2212 Superconductors - Deniz, E.; Ozturk, O.; Cavdar, Şükrü; Koralay, Haluk; Gunen, A.; Erdem, M. (Springer Science and Business Media LLC, 2012)
The effects of PbSe addition and heat treatment on the structure and mechanical properties of Bi-2212 superconductors are analyzed. Glass ceramic method is used to produce PbSe added samples. The mechanical properties are derived using Vickers microhardness measurement results. Well known analysis methods like Meyer’s law, PSR (Proportional Sample Resistance) Model, EDP (Elastic/Plastic Deformation Model), Hays-Kendall approach and IIC (Indentation-Induced Cracking Model) are used to calculate load independent microhardness values of the samples. HK approach produces successful results for the samples A, E, F, G and H indicating ISE (Indentation Size Effect) behavior. The IIC model successfully explains RISE (Reverse Indentation Size Effect) behavior for the samples B, C and D. RISE behavior is observed only for the samples where the plastic deformation is dominant. ISE behavior is observed for the samples where both elastic and plastic deformation are produced. The results of XRD and SEM analysis show improvement with PbSe addition in the crystal structures and surface morphologies of superconducting samples.
Keywords: XRD; Bi-2212; SEM; ISE; RISE; Vickers microhardness